Layer-by-Layer Fabrication of PAH/PAMAM/Nano-CaCO3 Composite Films and Characterization for Enhanced Biocompatibility - Naemi Tonateni Shifeta; Shindume Lomboleni Hamukwaya; Qi An; Huiying Hao; Melvin Mununuri Mashingaidze (International Journal of Biomaterials)
Nanoparticle production and functionalization for various biomedical uses are still challenging. Polymer composites constituted of poly(amidoamine) (PAMAM), polyallylamine hydrochloride (PAH), and calcium carbonate (CaCO3) nanoparticles have good biocompatibility with physiological tissue and fluids, making them excellent candidates for biomedical applications. This study investigated the characteristics of polymeric/nano-CaCO3 composite films based on a PAH/PAMAM matrix, which were fabricated through layer-by-layer synthesis on quartz glass substrates. It was found that the as-prepared elastic moduli of the resultant (PAH/PAMAM)n-CaCO3 (where n represents the number of bilayers) composite films varied from 1.40 to 23.70 GPa for different degrees of cross-linking when 0.1 M nano-CaCO3 particles were incorporated into the polymer matrix. The highly cross-linked (PAH/PAMAM)15-CaCO3 composite film had the highest recorded elastic modulus of 23.70 GPa, while it was observed that for all the composite films fabricated for the present study, the addition of the nano-CaCO3 particles approximately doubled the elastic modulus regardless of the degree of polymerization. Live/Dead assays were used to determine whether the produced composite films were compatible with human lung fibroblast cells. The findings indicate that the (PAH/PAMAM)7.5-CaCO3 composite film had the most positive effect on cell growth and proliferation, with the (PAH/PAMAM)15-CaCO3 composite film demonstrating significant ion transport behavior with low impedance, which was considered good for in vivo rapid cell-to-cell communication. Therefore, the (PAH/PAMAM)7.5-CaCO3 and (PAH/PAMAM)15-CaCO3 composite films are potential tissue engineering biomaterials, but further studies are essential to generate more data to evaluate the suitability of these composites for this and other biomedical functions.